A Courage, Victory, And Triumph Reflected In Danielle Steel's Winners 2013 Novel: A Humanistic Psychological Approach - Prastiwi, Lilis; , Titis Setyabudi, S.S.M.Hum (2016)
This study is proposed to reveal how courage, victory and triumph reflected in Winners (2013) novel by Danielle Steel. The objectives of this study are to analyze Lily's personality based on humanistic psychological approach and to analyze courage, victory and triumph according to the Winners (2013)novel by Danielle Steel's. The writer employs qualitative research. The writer uses two data sources: primary and secondary. The primary data source is about the novel itself. Then the secondary data are taken from other sources which are related to the primary data such as the literary books, dictionary, some articles related to the novel and website aboutWinners novel. The technique of data collection is library research. The technique of analyzing data is descriptive qualitative. Based on humanistic psychological analysis, Lily can show courage, victory and triumph because she can fulfill the five basic hierarchies of human needs by Abraham Maslow such as physiological needs, safety needs, belongingness and love needs, self-esteem needs and self-actualization needs.